Análise ambiental das infecções primárias de corrente sanguínea pelo complexo Acinetobacter baumannii-calcoaceticus identificadas laboratorialmente na região Centro-Oeste do Brasil - Rosniak, Fernanda Aparecida Monteiro da Silva Carboni (2021)
Introduction: Acinetobacter baumannii-calcoaceticus is an important hospital pathogen, mainly related to bloodstream infections that occur in intensive care units (ICU). Studies carried out especially in temperate regions have demonstrated the seasonal behavior of HAIs and that the highest incidences are related to high temperature and greater precipitation. The tropical climate, present in the Center-West region of Brazil, presents very specific characteristics of temperature and rainfall, which have not yet been investigated. Objectives: To analyze the mean incidence density of primary laboratory bloodstream infections (IPCSL) associated with the central venous catheter (CVC) caused by the carbapenem-resistant A. baumannii-calcoaceticus complex; Analyze the behavior of the incidence rate in the studied period and Evaluate the trend of the incidence density of IPCSL caused by the carbapenem-resistant A. baumannii-calcoaceticus complex and Correlate the average monthly incidence density of IPCSL with the monthly rainfall and average temperature. Method: Retrospective ecological study that was conducted from January 2014 to December 2019, in a capital city in the Midwest of Brazil. The data were collected from the IPCSL records of 49 pediatric and adult ICUs. The average monthly temperature and precipitation were obtained from the Instituto Nacional de Meteorologia - INMET. For data analysis, the following tests were used: linear regression analysis and exponential analysis, Pearson's test and Mann-Whitney test. For all tests, p<0,05; Significant. Results: There were 116 IPCSL caused by the carbapenem-resistant A. baumannii-calcoaceticus complex. There was no difference in incidence density between the summer (0.18±0.11) and winter (0.20±0.05) seasons (p = 0.748). The incidence density of IPCSL associated with CVC was 1.15 / 1,000 patient-days and the trend was decreasing with a decrease of 25.0% (p=0.015). There was a difference in average rainfall between the cold months (45.5±74.9 mm) and the warm months (198.1 ± 45.1) (p = 0.006). There was no difference in the average temperature between cold months (24.7 ± 1.8) and warm months (26.3 ± 0.4) (p = 0.054). There was no correlation between the incidence density of IPCSL with rainfall and temperature. Conclusion: it was observed that the trend in the incidence density of IPCLS was decreasing with a decrease of 25.0%. There was no correlation between climatic factors with the increase in the incidence density of IPCSL caused by the A. baumannii calcoaceticus complex